Protocol for the implementation of a self-assessment processes at UNED Business School Careers (Revista Electrónica Calidad en la Educación Superior, 2022)
This paper present the partial results of an investigation carried out to design protocol for the implementation of a self-assessment model, taking as a case study the Business School careers at UNED. The results to be presented are aimed at justifying the need to have practical instruments, to implement a self-assessment model, during the period February 2020 to May, 2021. The main findings indicate that the people consulted know the terms of self-assessment process and self-assessment model, however, they lack practical tools to follow up on them.
Keywords: Process; model; self-assessment; quality; careers; protocol